Lithium-Ion Transport in Nanocrystalline Spinel-Type Li[InxLiy]Br4 as Seen by Conductivity Spectroscopy and NMR - Gombotz, Maria; Rettenwander, Daniel; Wilkening, H. Martin R. (Frontiers in Chemistry, 2020)
Currently, a variety of solid Li+ conductors are discussed to serve as potential electrolytes in all4 solid-state Li-ion batteries and batteries using metallic Li as anode. Besides oxides, sulphides and thioposphates also halogenides, such as Li3YBr6, belong to the group of such promising materials. Here, we report on the mechanosynthesis of ternary, nanocrystalline (defect-rich) Li[InxLiy]Br4, which crystallizes with spinel structure. We took advantage of a soft mechanochemical synthesis route that overcomes limitations of classical solid-state routes which usually need high temperatures to prepare the product. X-ray powder diffraction, combined with Rietveld analysis, was used to collect first information of the crystal structure; it turned out that the lithium indium bromide prepared adopts cubic symmetry (Fd¯3m). The overall and electronic conductivity were examined via broadband conductivity spectroscopy and electrical polarisation measurements. While electric modulus spectroscopy yielded information on long-range ion transport, 7Li nuclear magnetic resonance (NMR) spin-lattice relaxation measurements revealed rapid, localized ionic hopping processes in the ternary bromide. Finally, we studied the influence of thermal treatment on overall conductivity, as the indium bromide might find applications in cells that are being operated at high temperatures (330 K and above).